A trajetória e as referências teóricas e de método de interpretação de Roger Brunet na construção da coremática: análises iniciais de uma decodificação - Eduardo Paulon Girardi (Confins)
In this paper, we identify and carry out the initial analyses of Roger Brunet's theoretical basis and interpretation/scientific method references on the construction of the chorematics. The emphasis was mainly on the references to the structuralist method and on the systemic approach, the two main methods of interpretation present in Brunet's work. This is the first publication of the results of research carried out in France in the first semester of 2023 and which is inserted in a larger project, which is the construction of the Critical Geographic Cartography (CGC) that we initially presented in 2008. To understand the details of Brunet's references on theory and method is indispensable to advance the proposal of the CGC in the context of Brazilian Geography.